1989
DOI: 10.1002/bip.360280307
|View full text |Cite
|
Sign up to set email alerts
|

Solvated helical backbones: X‐ray diffraction study of Boc‐Ala‐Leu‐Aib‐Ala‐Leu‐Aib‐OMe · H2O

Abstract: A second example of insertion of a water molecule into the helical backbone of an apolar peptide is presented here and compared to a similar occurrence in a longer peptide with the same type of sequence of residues, i.e., Boc-Aib-(Ala-Leu-Aib)3-OMe. The backbone of the title compound assumes an approximate 3(10)-helical form with three 4----1 hydrogen bonds. In the place of a fourth 4----1 hydrogen bond, a water molecule is inserted between O(1) and N(4), and acts as a bridge by forming hydrogen bonds N(4) ...… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The frequencies of the 1652 and 1642 cm'1 bands assigned to -helix in the undeuterated and deuterated peptide, respectively, are both low for regular -helices. Karle et al (1989b,c) reported the insertion of water molecules into the helical backbone of the apolar peptides Boc-Ala-Leu-Aib-Ala-Leu-Aib-OMe (Karle et al, 1989b) and Boc-Aib-(Val-Ala-Leu-Aib)3-OMe (Karle et al, 1989c) when each was crystallized individually. In the first example, H-bonds are formed between the water and the C=0 and NH groups of the Ala residues.…”
Section: Discussionmentioning
confidence: 99%
“…The frequencies of the 1652 and 1642 cm'1 bands assigned to -helix in the undeuterated and deuterated peptide, respectively, are both low for regular -helices. Karle et al (1989b,c) reported the insertion of water molecules into the helical backbone of the apolar peptides Boc-Ala-Leu-Aib-Ala-Leu-Aib-OMe (Karle et al, 1989b) and Boc-Aib-(Val-Ala-Leu-Aib)3-OMe (Karle et al, 1989c) when each was crystallized individually. In the first example, H-bonds are formed between the water and the C=0 and NH groups of the Ala residues.…”
Section: Discussionmentioning
confidence: 99%
“…may be involved in ion channels formed by helices with predominantly apolar residues, or they may be involved in the helix-folding or unfolding processes. Observations of water insertions have also been made in the apolar structures of Boc-(Ala-Leu-Aib)2-OMe and Boc-Val-Ala-Leu-Aib-VaI-Ala-Leu-OMe (Karle, Flippen-Anderson, Uma & Balaram, 1989b, 1990c. In the latter structure, both the unhydrated and the hydrated backbones occur side by side in the same unit cell.…”
Section: Water Penetration Into Helix Backbonesmentioning
confidence: 99%
“…'7~'8 Crystal structures of peptides [19][20][21] and proteins22 have yielded a static view of the modes of hydration of helix backbones. The stabilization of helices in short peptides is readily achieved by the incorporation of a-aminoisobutyryl ( Aib) residues, which are constrained to adopt a limited range of 6, $ values, as a consequence of the presence of the additional methyl group at the C a atom.23s24 Extensive studies of Aib-containing peptides emphasize the role of this residue in promoting @-turn and 310-helical conformations in short pep tide^^^*'^ and 310-and a-helical structures in larger sequence^.^^.^^ Interestingly, even a single centrally placed Aib residue in [6][7][8][9] (7) 3476 (8) 3839 (10) 2946 (8) 3950 (10) 3197 (17) 9440 (6) 9846 (8) 9806 (12) 9752 (20) 9683 (16) 9995 (25) 10070 (16) 10255 (17) 10335 (9) 6833 (20) 141 (11) 8324 (20) 161 (12) 3472 (13) 105 (6) 2503 (18) 134 (10) 3851 (8) 76 (4) 9224 (49) 344 (57) 10119 (16) 168 (12) 8841 (14) 139 (11) 8436 (26) 41 (9) 8805 (29) 79 (14) 8069 (23) 83 (14) 8932 (30) 95 (28) 8512 (11) 117 (6) 9022 (26) 140 (19) 8696 (31) 164 (33) 10009 (51) 189 …”
Section: Introductionmentioning
confidence: 99%